The Development of Nature and Culture-Themed Accommodation in Jatiluwih: Opportunities and Challenges - Kesawa Udayana; Rimalinda Lukitasari; Dinar Sukma Pramesti; Vivi (INSPIRE : Journal of Culinary, Hospitality, Digital & Creative Arts and Event, 2025)
Jatiluwih, located in Tabanan Regency, Bali, is renowned for its terraced rice fields and the traditional subak irrigation system, which has been inscribed as a UNESCO World Cultural Heritage since 2012. This uniqueness makes Jatiluwih a strategic site for the development of nature- and culture-themed accommodation aligned with the principles of sustainable tourism. This article aims to analyze the opportunities and challenges of such development. A qualitative descriptive method was employed, using interview and literature analysis. The findings reveal considerable opportunities in terms of natural and cultural appeal, stable international tourist demand, and community empowerment potential. However, challenges remain in the form of infrastructure limitations, cultural commodification risks, environmental degradation, and stringent regulations. The study concludes that multi-stakeholder collaboration involving government, investors, and local communities is crucial to ensure that accommodation development in Jatiluwih not only drives economic benefits but also safeguards cultural authenticity and environmental sustainability.